Desorption and crystallization kinetics in nanoscale thin films of amorphous water ice - Scott Smith, R.; Huang, C.; Wong, E.K.L.; Kay, Bruce D. (Surface science, 1996)
The amorphous to crystalline ice phase transition is studied by measuring the water desorption rate from nanoscale thin films of water vapor deposited on Au(111) and Ru(001) single crystal metallic substrates. The desorption kinetics are substrate dependent and suggest strongly that the film morphology is governed by the hydrophilicity of the substrate. The crystallization kinetics are independent of substrate but depend strongly on both temperature and film thickness and are consistent with a spatially random nucleation and isotropic growth model.